Cyclic fluctuation of blood pressure in neonatal neuroblastoma. Issue 6 (18th December 2014) - Fujishiro, Jun; Sugiyama, Masahiko; Ishimaru, Tetsuya; Uotani, Chizue; Tsuchida, Shinya; Takahashi, Naoto; Shiozawa, Ryosuke; Takita, Junko; Iwanaka, Tadashi
Abstract: Herein is described a case of neonatal neuroblastoma with cyclic blood pressure fluctuation and elevated catecholamines. The fluctuations stabilized after treatment with α‐adrenergic blocker and the perioperative course was uneventful. The possibility of catecholamine‐related symptoms including hypertension, heart failure, and blood pressure fluctuations should be considered in the treatment for neuroblastoma; if they are present, treatment with α‐blockers is effective.